Analisis Kesulitan Belajar Fisika Materi Elastisitas Dan Hukum Hooke Dalam Penyelesaian Soal - Soal Fisika - Alpiana Hidayatulloh (Universitas Hamzanwadi, 2020)
This research aim to analyzw the difficulties faced by XI grade students of MA Yadaro when working on physics problems. Research subject totaled 13 studen. To see the difficulties faced by studens an evaluation testwas conducted in the form of a written test with 5 essay question. Then teh results of the evaluation when analyzed by means of qualitative description analysis. Based on the results of data analysis, the difficulty of students in stage I reached 83.93%, for stage II it reached 86.67%, stage III reached 99.98% while for stage IV it reached 5.0%. The cause of the difficulties experienced by students is that students do not know the use of the formula used, do not understand mathematical operations in solving mathematical problems.DOI: 10.29408/kpj.v4i1.1636